Perancangan Prototype Sistem Pendeteksi Stunting dengan Menggunakan Microcontroller Berbasis Sensor Ultrasonic dan Load cell - Fahmi Fadillah; Hamzah Nurrifqi Fakhri F; Yosep Bustomi (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
Stunting disease describes abnormalities in a child's body caused by impaired physical growth. Research has been carried out on Stunting which produces the causal factors and long-term risks for Stunting sufferers. It is hoped that there will be technology that can detect Stunting growth early on in children, so that it can be treated quickly. Therefore, it is necessary to design a Prototype Stunting Detection System using a Microcontroller Based on Ultrasonic Sensors and Load cells which aims to identify Stunting factors for children in the Posyandu working area of ​​Garut Regency. The methodology used is a Prototype Model and uses a black box testing method. As a result, the existence of this Stunting detection system Prototype contributes to Posyandu officers and children so that they can be detected early so that later prevention can be carried out so that it does not grow until the child is old, so that the percentage of Stunting growth can decrease.